1997
DOI: 10.1007/s11661-997-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial characteristics for brazing of aluminum matrix composites with Al-12Si filler metals

Abstract: Discussions concerning the interfacial reactions and characterizations in brazing aluminum matrix composites are documented in this study. Joints of alumina particulate reinforced 6061 aluminum matrix composites were made using an Al-12 (wt pct) Si filler metal by vacuum brazing. The resulted maximum bonding strengths were 75.4, 81.5, and 71.8 MPa for 10, 15, and 20 vol pct alumina reinforcement, respectively. The microstructural examinations revealed that the bonding strength was strictly related to the reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…4a and b). Such voids were also found when brazing of Al-MMCs containing alumina particles [10]. So it was concluded that the wettability of filler metal on SiC particles is not always good when brazing at 550 • C. With the brazing temperature raised to 560 • C, the flowability and activity of the filler metal were substantially improved (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…4a and b). Such voids were also found when brazing of Al-MMCs containing alumina particles [10]. So it was concluded that the wettability of filler metal on SiC particles is not always good when brazing at 550 • C. With the brazing temperature raised to 560 • C, the flowability and activity of the filler metal were substantially improved (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Although researchers [10,11] have investigated the joining of Al-MMCs reinforced with low volume fractions of reinforcements by direct brazing and the results are reasonably good, the direct brazing of Al-MMCs reinforced with high volume fractions of reinforcements have not been reported. In this work, an Al-Cu-Mg-Si-Ni alloy was used as the filler metal to braze an Al-MMC with a high volume fraction of SiC particles.…”
Section: Introductionmentioning
confidence: 99%
“…A great affinity of aluminum for oxygen requires that aggressive fluxes be used to remove a layer of oxides Al 2 O 3 from the specimen surface before soldering [10][11][12][13].…”
Section: Limitations In Soldering Aluminum Foamsmentioning
confidence: 99%
“…Particulates reinforced aluminum matrix composites (PRAMCs) exhibit high specific stiffness and strength to weight ratio at room and elevated temperatures, and thus possess potential structural applications in the aerospace and automotive industries [3]. However, it is difficult to achieve high-performance joints of PRAMCs by using conventional fusion welding, brazing and transient liquid phase diffusion welding (TLP-DW) [4][5][6][7]. The previous researches on FSW indicated that the joint efficiency of PRAMCs was between 80% and 97% [3,8].…”
Section: Introductionmentioning
confidence: 99%